HUBUNGAN STRATEGI PEMBELAJARAN DENGAN KEMAMPUAN PELAJAR LUAR BIASA - Rahmayani Bancin; Muhammad Sholeh; Fauziah Nasution (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This study aims to determine the relationship between learning strategies and outstanding student abilities. The type of writing in scientific writing is library research, namely writing based on the results of various literature studies to obtain formulations and conclusions that are arranged descriptively to answer the problems raised in the paper. The abilities that must be possessed by extraordinary students are Critical Thinking (Critical Thinking), Communication (communication), Creativity (creativity) and Collaboration (collaborating). The relationship between learning strategies and outstanding learner abilities.